ANALYSIS OF SUSTAINABLE PUBLIC PROCUREMENT OF THE ENVIRONMENT SECRETARIAT OF SÃO PAULO STATE (Gestão & Regionalidade, 2018)
The goal is to analyze the implementation and operation of sustainable public procurement in the Secretariat of Environment of São Paulo (SMA). In sustainable procurement include environmental criteria in tenders. An exploratory and descriptive research with a qualitative approach to sustainable procurement in the SMA was held. Documents were analyzed, file records and interviews. The state of São Paulo is one of the most organized in terms of sustainable procurement and the SMA together information both in state terms and in terms of their own office. In the state of São Paulo is considered sustainable procurement product or service that has the Environmental Seal and / or edict that includes social and environmental criteria. The analysis showed SMA's efforts to realize sustainable public procurement, however identified some problems regarding its real environmental contribution. It should be noted that there is no classification of sustainable bids (it is considered to include any sustainable criteria) and that there is no professionalization (lack of standardization and research). Keywords: Sustainable procurement; implementation; operation.